If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2 + -2(x + 4) + 4 = 2 Reorder the terms: 2 + -2(4 + x) + 4 = 2 2 + (4 * -2 + x * -2) + 4 = 2 2 + (-8 + -2x) + 4 = 2 Reorder the terms: 2 + -8 + 4 + -2x = 2 Combine like terms: 2 + -8 = -6 -6 + 4 + -2x = 2 Combine like terms: -6 + 4 = -2 -2 + -2x = 2 Solving -2 + -2x = 2 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '2' to each side of the equation. -2 + 2 + -2x = 2 + 2 Combine like terms: -2 + 2 = 0 0 + -2x = 2 + 2 -2x = 2 + 2 Combine like terms: 2 + 2 = 4 -2x = 4 Divide each side by '-2'. x = -2 Simplifying x = -2
| -5(5y-6)-y=-4(y-4) | | r^2-15r+56=0 | | -(-4+5x)=2(x+2) | | 270x/5=60 | | (x+3)(2x^2-5x+7)= | | 12+3(x-4)-2=7[5-4(4-x)] | | 6x-15+3x=2+9x-16 | | 2/3m+4=8 | | 2(X+4)/3=5X-1 | | 7-21a=15-25a | | 3/2x+1=9/3x | | 5x+8=2(2x+5) | | .2(x+.6)=.4(x-4.2) | | 30=120v/(v+60) | | b^2=-32-12b | | (a+2)(3a-4)= | | x/8+20=24 | | 4X+5.2X+4=0 | | -6-3(1+4b)=-2(-4+7b)+5 | | 6x+3x=90 | | -(x+8)+9=7x+1-8x | | -2x-2y=-26 | | 5(X-7)+25=7X-(2X+4)-6 | | 406=79.8+4w | | (2x+1)(3y-4)= | | 10m^3n^4-5m^2n+25m=0 | | 5(1+5k)=-33+6k | | -9x-27(x+4)=-5(7x+3) | | 7x^3+4x+x^3/2-4x | | 79.8=4w-7 | | 2(x+2)=6x+3-4x+1 | | 2x-142+x+16=180 |